Colonialism and elitism in Philippine political development assessing the roots of underdevelopment - Buendia, Rizal G. (1993)
Philippine political development has been shaped by its colonial history and postcolonial elitist political system. As the country is ushered into the 21st century, the problems of underdevelopment remain. These problems are rooted on the unresolved question of nationhood, skewed concept of public service, alienated political system, and ambivalent political culture. These problems contributed significantly to the weakness of the country's political and economic institutions. If national devel- opment has to transpire, the spirit of nationalism subdued by long periods of colonialism must be revived, the political system must be democratized, and an ethic-oriented politics towards the well-being of the people must emerge. Through these efforts, Philippine sovereignty can be defended, foreign intervention can be curtailed, national honor and pride can be redeemed, and a better society for the coming generations can be created.
Keywords: Imperialism; Political development; Elitism; Philippines -- Politics and government